Position and stabilization control of inverted pendulum systems using sliding mode based control and observer - Heo, Junseo; Chwa, Dongkyoung (Transactions of the Korean Institute of Electrical Engineers, 2019)
This paper proposes a position and stabilization control method for the inverted pendulum systems with disturbances such that an unstable equilibrium point is maintained and the position of the actuated body that can move freely is controlled. It is difficult to design the controller due to the dynamic coupling and nonlinear characteristics of the underactuated systems because the degree of freedom of the system is more than the number of the actuators. It is also a difficult problem to compensate for the disturbance. To solve this problem, we introduced an integral sliding mode based observer. Observer can be used to estimate and compensate for disturbance and system model errors, and state variables can also be estimated. Sliding mode controller for position and stabilization control is also proposed. Controller consists of the part that generates a reference value for the pendulum to move the actuated body to the desired position and the part that generates a control input to make the angle of the pendulum track the reference value. The stability of the overall pendulum systems using the proposed control schemes is provided and the feasibility of the proposed control methods is demonstrated through simulation results.
Keywords: Integral sliding mode; Inverted pendulum; Inverted pendulum system; Lyapunov stability; Nonlinear characteristics; Sliding mode controller; Tracking controls; Unstable equilibrium points; Integral sliding mode observer; Inverted pendulum; Lyapunov stability; Sliding mode control; Tracking control